Chronic proliferative rhinitis associated with Salmonella enterica subsp. diarizonae serovar 61:k:1, 5, (7) in a sheep from Romania: First documented case in Southeastern Europe - Adrian-Valentin Potârniche; Emilia Trif; Constantin Cerbu; Emöke Páll; Andrada Negoescu; Cristina Borfălău; Sorin Marian Mârza; Lucia Bel; Florica Bărbuceanu; Marcelo de las Heras; Delia Lacasta; Marian Taulescu (Veterinary Research Communications, 2026)
A case of chronic proliferative rhinitis (CPR) associated with Salmonella enterica subsp. diarizonae serovar 61:(k):1 , 5 , (7) (SED) is described in a 3-year-old ewe from the university teaching farm in Transylvania, Romania. Clinical examination revealed bilateral seromucous nasal discharge and visible proliferative masses within both nasal cavities. Infrared thermography demonstrated increased heat emission over the nasal region, consistent with active inflammation. Computed tomography imaging showed marked proliferative invasion within the ventral nasal turbinates. Histopathology and immunohistochemistry confirmed chronic proliferative rhinitis characterized by fibrovascular tissue proliferation, epithelial cell hyperplasia, and mixed inflammatory cell infiltrate, predominated by lymphocytes, plasma cells and macrophages. SED was isolated as the sole microorganism from nasal swabs and confirmed by serotyping, PCR, and immunohistochemistry. To the authors’ knowledge, this is the first documented case of CPR associated with SED in Romania and in Southeastern Europe, highlighting the need to include CPR among the differential diagnoses for adult sheep with chronic upper respiratory disease, and to include SED within its aetiological agents.